2021
DOI: 10.1136/bmjgh-2021-005537
|View full text |Cite
|
Sign up to set email alerts
|

The influence of gender and ethnicity on facemasks and respiratory protective equipment fit: a systematic review and meta-analysis

Abstract: IntroductionBlack, Asian and minority ethnic (BAME) people are disproportionately affected by COVID-19. Respiratory protective equipment (RPE) has conventionally been developed for a predominantly white male population that does not represent the healthcare workforce. The literature was reviewed to determine the protection offered to female and BAME users.MethodsFive databases were searched. Eligible studies related to respirator fit in the context of anthropometrics, gender and ethnicity. Meta-analysis was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
29
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 67 publications
0
29
0
2
Order By: Relevance
“…Hariharan et al were also interested in the effect of anthropometric differences on the fit of respirators and found that the fit varied between faces, therefore, resulting in a different distribution of leakage through the respirator's perimeter [26]. Chopra et al studied a compilation of literature on the effects of anthropometric differences on mask leakage and found that gender-based anthropometric differences are associated with lower mask efficacy in half of the studies [27]. Anthropometric difference is also significant across ethnicities, and Chopra et al stated that, although minority groups are disproportionately affected by the COVID-19 pandemic, they are under-represented in literature [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hariharan et al were also interested in the effect of anthropometric differences on the fit of respirators and found that the fit varied between faces, therefore, resulting in a different distribution of leakage through the respirator's perimeter [26]. Chopra et al studied a compilation of literature on the effects of anthropometric differences on mask leakage and found that gender-based anthropometric differences are associated with lower mask efficacy in half of the studies [27]. Anthropometric difference is also significant across ethnicities, and Chopra et al stated that, although minority groups are disproportionately affected by the COVID-19 pandemic, they are under-represented in literature [27].…”
Section: Introductionmentioning
confidence: 99%
“…Chopra et al studied a compilation of literature on the effects of anthropometric differences on mask leakage and found that gender-based anthropometric differences are associated with lower mask efficacy in half of the studies [27]. Anthropometric difference is also significant across ethnicities, and Chopra et al stated that, although minority groups are disproportionately affected by the COVID-19 pandemic, they are under-represented in literature [27].…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Ng and colleagues, ethnic background was known for only 493 participants (23%: European background, 13%; non‐European, 10%), which could have implications for interpreting the study. The authors of a recent systematic review found that Black, Asian, and people with minority ethnic backgrounds are under‐represented in respirator research 10 . Their findings were limited by small sample sizes, heterogeneity, and inadequate reporting in the included studies, but some people with non‐European ethnic backgrounds, who comprise a large proportion of health care workers, have facial features that can affect respirator fit 10 …”
mentioning
confidence: 99%
“…The authors of a recent systematic review found that Black, Asian, and people with minority ethnic backgrounds are under-represented in respirator research. 10 Their findings were limited by small sample sizes, heterogeneity, and inadequate reporting in the included studies, but some people with non-European ethnic backgrounds, who comprise a large proportion of health care workers, have facial features that can affect respirator fit. 10 Ng and colleagues report considerable differences in the performance of the included respirators, including their fit test pass rates: 96.4% for the three-panel, flat-fold respirator, 65.0% for the semi-rigid cup respirators, 32.4% for the flat-fold respirator, and 59.2% for the duckbill respirators.…”
mentioning
confidence: 99%
See 1 more Smart Citation